Kearifan Lokal Dalam Ajaran Islam Wetu Telu di Lombok - Zaki Yamani Athhar (Ulumuna, 2005)
Islam was not present in an empty-peopled place. It was revealed by God onto a community that had had its own way of life, belief system, and religious practices which are artificially or fundamentally different from it. In that context, Islam—since the very beginning of its history and will continuously last to the end of time—has faced some different even contradictive values of local traditions and cultures. It leads to a kind of dialectical processes, and in turn produces what is called local Islam such as Islam Wetu Telu in Bayan, West Lombok. In addition to revealing historical root of Islam Wetu Telu through historical approach, this article also describes its structure of belief, and ritual practices that are currently applied. Religious practices of Islam Wetu Telu consist of four main rituals as follows upacara negara, rituals related to agricultural activities, upacara desa, and rituals related to its religious almanac cycle. The community of Islam Wetu Telu has its own social structure that may be different from other communities in Lombok.